Staged Revision with Antibiotic Spacers for Infected Hindfeet vs One-Stage Revision Using an Ilizarov Ringfixator: What's Better?. Issue 4 (16th October 2019) - Hartmann, Rebecca; Grubhofer, Florian; Wirth, Stephan
Category: Hindfoot Introduction/Purpose: The treatment of hindfeet infections with a two-stage revision surgery using an antibiotic-loaded cement spacer is an established treatment strategy. If the soft tissue situation is critical or if patients do have severe comorbidities, the use of a one-stage procedure, using an Ilizarov ringfixator to perform the arthrodesis is also an option. We wanted to compare the outcome of patients who either received the two-stage revision or the one-stage procedure. The purpose of the study was to determine the likelihood of infection control and radiological consolidation of the arthrodesis after either two-stage or one-stage revision in patients with hindfoot infection, as defined by the Musculoskeletal Infection Society PJI criteria. The postoperative AOFAS score was used to measure the clinical outcome. Methods: Between 1995 and 2015, we treated 12 patients with a two-stage procedure using an antibiotic-loaded cement spacer, followed by antibiotic therapy. The second stage consisted of a hindfoot arthrodesis. Of those, 7 were available for review at a minimum of 24 months. 3 were excluded because they were deceased (due to old age). Two moved abroad, leaving 7 patients for analysis. During the same time period we treated 13 patients with a one-stage hindfoot arthrodesis using an Ilizarov ringfixator. Of those, 10 were available for review at a minimum of 24 months. 2 were excluded because they were deceased due to old age, leaving 10 patients for analysis. The primary outcome included the proportion of patients achieving infection control, defined as the absence of the Musculoskeletal Infection Society PJI criteria. Radiological consolidation on standard foot X-rays was also determined. The clinical outcome was assessed with the AOFAS hindfoot score. Results: Successful infection control in the two-stage revision group was achieved in 6 out of 7 patients (86%). One patient achieved infection control only after a below-knee amputation. The mean AOFAS score at the latest follow-up was 75. Radiological consolidation was achieved in 70% (5 out of 7, with one patient needing an amputation for infection control). In the Ilizarov-group, successful infection control was achieved in 9 out of 10 patients (90%). One patient achieved infection control only after a below-knee amputation. The mean AOFAS score at the latest follow-up was 70. Radiological consolidation was achieved in 80% (8 out of 10, with one patient needing an amputation for infection control). Conclusion: A one-stage arthrodesis using an Ilizarov ringfixator for infection control in infected hindfeet leads to comparable infection control and radiological consolidation as the established two-stage procedure with an antibiotic-loaded cement spacer. The clinical outcome, measured by the AOFAS hindfoot score, is also comparable in both groups. The one-stage procedure using an Ilizarov ringfixator should therefore be considered as a treatment option, when soft tissues or comorbidities do not allow a two-stage procedure. It is an option to avoid a below-knee amputation in those patients.